High performance computing in science and engineering '08: transactions of the High Performance Computing Center, Stuttgart (HLRS) 2008 - Nagel, Wolfgang E.; Kröner, Dietmar B.; Resch, Michael (Springer Berlin Heidelberg, 2009)
Physics -- Magnetic Fields in Very Light Extragalactic Jets -- The SuperN-Project: Status and Outlook -- Massless Four-Loop Integrals and the Total Cross Section in e + e ? Annihilation -- Solid State Physics -- Computer Simulations of Complex Many-Body Systems -- Quantum Confined Stark Effect in Embedded PbTe Nanocrystals -- Signal Transport in and Conductance of Correlated Nanostructures -- Supersolid Fermions Inside Harmonic Traps -- Chemistry -- Azobenzene–Metal Junction as a Mechanically and Opto–Mechanically Driven Switch -- A Density-functional Study of Nitrogen and Oxygen Mobility in Fluorite-type Tantalum Oxynitrides -- Molecular Modeling and Simulation of Thermophysical Properties: Application to Pure Substances and Mixtures -- Flow with Chemical Reactions -- A Hybrid Finite-Volume/Transported PDF Model for Simulations of Turbulent Flames on Vector Machines -- Numerical Investigations of Model Scramjet Combustors -- Computational Fluid Dynamics -- Direct Numerical Simulation of Film Cooling in Hypersonic Boundary-Layer Flow -- Two-Point Correlations of a Round Jet into a Crossflow – Results from a Direct Numerical Simulation -- The Influence of Periodically Incoming Wakes on the Separating Flow in a Compressor Cascade -- Turbulence and Internal Waves in a Stably-Stratified Channel Flow -- High Resolution Direct Numerical Simulation of Homogeneous Shear Turbulence -- Direct Numerical Simulation (DNS) on the Influence of Grid Refinement for the Process of Splashing -- Implicit LES of Passive-Scalar Mixing in a Confined Rectangular-Jet Reactor -- Wing-Tip Vortex / Jet Interaction in the Extended Near Field -- Impact of Density Differences on Turbulent Round Jets -- Thermal & Flow Field Analysis of Turbulent Swirling Jet Impingement Using Large Eddy Simulation -- Hybrid Techniques for Large–Eddy Simulations of Complex Turbulent Flows -- Vector Computers in a World of Commodity Clusters, Massively Parallel Systems and Many-Core Many-Threaded CPUs: Recent Experience Based on an Advanced Lattice Boltzmann Flow Solver -- Numerical Modeling of Fluid Flow in Porous Media and in Driven Colloidal Suspensions -- Numerical Characterization of the Reacting Flow in a Swirled Gasturbine Model Combustor -- Numerical Simulation of Helicopter Aeromechanics in Slow Descent Flight -- Partitioned Fluid-Structure Coupling and Vortex Simulation on HPC-Systems -- FEASTSolid and FEASTFlow: FEM Applications Exploiting FEAST’s HPC Technologies -- Overview on the HLRS- and SSC-Projects in the Field of Transport and Climate -- Effects of Intentional and Inadvertent Hygroscopic Cloud Seeding -- The Agulhas System as a Key Region of the Global Oceanic Circulation -- HLRS Project Report 2007/2008: “Simulating El Nino in an Eddy-Resolving Coupled Ocean-Ecosystem Model” -- Structural Mechanics -- Numerical Studies on the Influence of Thickness on the Residual Stress Development During Shot Peening -- A Transient Investigation of Multi-Layered Welds at Large Structures -- High Performance Computing and Discrete Dislocation Dynamics: Plasticity of Micrometer Sized Specimens -- Miscellaneous Topics -- Molecular Modeling of Hydrogen Bonding Fluids: New Cyclohexanol Model and Transport Properties of Short Monohydric Alcohols -- Investigation of Process-Specific Size Effects by 3D-FE-Simulations -- Andean Orogeny and Plate Generation -- Hybrid Code Development for the Numerical Simulation of Instationary Magnetoplasmadynamic Thrusters -- Doing IO with MPI and Benchmarking It with SKaMPI-5.